How do you solve the system 5x – 3y = 13 and 4x – 3y = 11?

2 Answers
May 21, 2018

x=2 and y=-1

Explanation:

After subtracting second equation from first one,

(5x-3y)-(4x-3y)=13-11

x=2

Hence,

5*2-3y=13

10-3y=13

-3y=3, thus y=3/(-3)=-1

May 21, 2018

(2, -1)

Explanation:

Solving by Elimination

Multiply the first equation by -1 to temporarily eliminate y. Then add to the second equation (unmodified).

-(5x - 3y = 13)
-5x + 3y = -13
4x - 3y = 11

-x = -2
x = 2

Substitute into either equations to solve for y
5(2) - 3y = 13
10 - 3y = 13
- 3y = 3
y = -1

Answer: (2, -1)